Percepciones y vivencias frente al climaterio en Mujeres atendidas en el Hospital II-2- Tarapoto, Periodo Julio-Setiembre 2014 - Dávila Sánchez, Kelly (2015)
The present study aimed to determine the perceptions and experiences against the Climacteric in women treated at the Hospital II-2-Tarapoto. July to September 2014 a Simple quantitative, descriptive cross-sectional study with prospective data collection Was performed. The sample consisted of 66 climacteric women (35-65 years) who Met the inclusion and exclusion criteria. To measure the varying perceptions and Experiences, was used as the structured survey method, and for processing and data Analysis, designed a database in Excel 2010. The results achieved are: The average Age of women at climacteric stage in Hospital II-2 Tarapoto is 47 years; 48.5% are Living together, 40.9% are Catholic; and 60.6% had secondary level studies. With Regard to the experiences of women in the climacteric period, 18.2% considered as a Cause of the disappearance or decrease in sexual activity; that the major signs and Symptoms of menopause are hot flashes, vaginal dryness; and decreased sexual Appetite. Regarding perceptions, 66.7% believe that the treatment at home is normal; 21.2% consider that the menopause negatively affects their social relationships. 48.5% also considered as positive aspects of the climacteric the absence of Menstruation and disregard for contraception. Concluding: perceptions and Experiences of menopause mostly not affect the life, health and development of Women